1977
DOI: 10.1210/endo-101-3-841
|View full text |Cite
|
Sign up to set email alerts
|

Aromatization and 5α-Reduction of Androgens in Discrete Hypothalamic and Limbic Regions of the Male and Female Rat1

Abstract: The in vitro aromatization and 5alpha-reduction of androgens to estrogens and dihydrotestosterone (DHT) were determined in incubations of microdissected brain regions of male and female gonadectomized, adrenalectomized rats. Metabolites formed from [1alpha,2alpha-3H]androstenedione or [1alpha,2alpha-3H]testosterone were purified by celite liquid-liquid partition chromatography, silica gel chromatography and recrystallization to stable 3H/14C ratios. The medial preoptic nucleus-anterior hypothalamic nucleus exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
68
0

Year Published

1979
1979
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(77 citation statements)
references
References 36 publications
9
68
0
Order By: Relevance
“…However, factors other than estrogen also may influence performance on a mental rotation task, because the correlation coefficient between estradiol and the slope was not high (though it was significant) in the present study. The subjects with a lower estradiol level may have a higher dihydrotestosterone (DHT) level, since DHT, an androgen, has been known to inhibit aromatization to estradiol (Selmanoff et al, 1977). The supplementation of DHT has been observed to improve spatial 22 Relationships between Estradiol and Mental Rotation memory (Cherrier et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…However, factors other than estrogen also may influence performance on a mental rotation task, because the correlation coefficient between estradiol and the slope was not high (though it was significant) in the present study. The subjects with a lower estradiol level may have a higher dihydrotestosterone (DHT) level, since DHT, an androgen, has been known to inhibit aromatization to estradiol (Selmanoff et al, 1977). The supplementation of DHT has been observed to improve spatial 22 Relationships between Estradiol and Mental Rotation memory (Cherrier et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The demonstration that testosterone can be metabolized to dihydrotestosterone (20) and to estradiol (21) in the hypothalamus, as well as in other tissues, suggested the possibility that the stimulatory effect of testosterone on GnRH release might require the conversion of testosterone to dihydrotestosterone or estradiol. Treatment of castrated rats with either dihydrotestosterone or estradiol prevented the fall in GnRH release.…”
Section: Discussionmentioning
confidence: 99%
“…Secretion of luteinizing hormone (LH)l and of folliclestimulating hormone (FSH) by the pituitary gland Received for publication 21 August 1978 and in revised form 23 October 1978.…”
Section: Introductionmentioning
confidence: 99%
“…However, the ability of estrogens and androgens to work in tandem to regulate male behavior was confirmed by investigators who demonstrated that co-treatment of castrated male animals with estradiol and dihydrotestosterone restored all parameters of male sexual behavior comparable to that of animals treated with testosterone alone (Baum and Vreeburg, 1973). Several brain regions important for controlling male sexual behavior contain aromatase activity (Naftolin, 1975, Selmanoff, 1977, Roselli et al, 1998 providing support for the concept that testosterone can be converted locally to estradiol within selective brain sites. Recent studies using the aromatase null mouse model (ArKO) underscore the importance of brain aromatase and estrogen in male rodent sexual behavior.…”
Section: Introductionmentioning
confidence: 90%
“…This relationship is based on numerous observations made over the years that testosterone can be converted to estradiol in a number of tissues, including brain (Naftolin et al, 1975), by the P450 enzyme, aromatase. Further, testosterone can also be converted to a more potent androgen, dihydrotestosterone, by the 5-alpha reductase enzyme (Selmanoff et al, 1977). Studies have shown that the metabolism of testosterone to estradiol is often critical for its behavioral actions in males, thus dispensing with the notion that estrogen is a "female hormone".…”
Section: Introductionmentioning
confidence: 99%